Beneficial Effects of Exogenous Melatonin and Dopamine on Low Nitrate Stress in Malus hupehensis - Du, Peihua; Yin, Baoying; Cao, Yang; Han, Ruoxuan; Ji, Jiahao; He, Xiaolong; Liang, Bowen; Xu, Jizhong (Frontiers in Plant Science, 2022)
Malus hupehensis, as an apple rootstock, is an economically important tree species popular due to its excellent fruit yield and stress resistance. Nitrogen is one of the critical limiting factors of plant growth and fruit yield, so it is crucial to explore new methods to improve nitrogen use efficiency. Melatonin and dopamine, as multifunctional metabolites, play numerous physiological roles in plants. We analyzed the effects of exogenous melatonin and dopamine treatments on the growth, root system architecture, nitrogen absorption, and metabolism of M. hupehensis when seedlings were exposed to nitrate-deficient conditions. Under low nitrate stress, plant growth slowed, and chlorophyll contents and 15NO3− accumulation decreased significantly. However, the application of 0.1 μmol/L melatonin or 100 μmol/L exogenous dopamine significantly reduced the inhibition attributable to low nitrate levels during the ensuing period of stress treatment, and the effect of dopamine was more obvious. In addition to modifying the root system architecture of nitrate-deficient plants, exogenous melatonin and dopamine also changed the uptake, transport, and distribution of 15NO3−. Furthermore, both exogenous melatonin and dopamine enhanced tolerance to low nitrate stress by maintaining the activity of enzymes (NR, NiR, GS, Fd-GOGAT, and NADH-GOGAT) and the transcription levels of related genes involved in leaf and root nitrogen metabolism. We also found that exogenous melatonin and dopamine promoted the expression of nitrate transporter genes (NRT1.1, NRT2.4, NRT2.5, and NRT2.7) in nitrate-deficient plant leaves and roots. Our results suggest that both exogenous melatonin and dopamine can mitigate low nitrate stress by changing the root system architecture, promoting the absorption of nitrate, and regulating the expression of genes related to nitrogen transport and metabolism. However, according to a comprehensive analysis of the results, exogenous dopamine plays a more significant role than melatonin in improving plant nitrogen use efficiency.